Inclined stress corrosion cracks in gas pipeline steels: morphology and implications. Issue 10 (24th October 2014) - Zadow, L.; Gamboa, E.; Lavigne, O.
<x xml:space="preserve">Abstract</x> A systematic morphological survey was carried out on 120 stress corrosion cracks (SCC) from an ex service X65 Australian gas pipeline. Out of these cracks, 81% showed a tendency to grow into the material away from the perpendicular. The inclined crack path was suggested to be due to anisotropic residual stress/strains present in the material introduced during pipe manufacturing processes. The overall depth of inclined SCC cracks was found to follow a logarithmic relationship to the SCC surface crack length. Hoop travel was defined as the distance that the crack tip travels in the pipe hoop direction as it grows into the material. The specific hoop travel distance was found to follow a linear relationship as a function of the SCC surface crack length. The relationships between surface crack length to through‐wall crack depth and hoop travel could allow pipe operators to formulate a worst case scenario for the purposes of SCC assessment and management.